The pull of the Central Flyway? Veeries breeding in western Canada migrate using an ancestral eastern route. Issue 3 (9th August 2017) - Kardynal, Kevin J.; Hobson, Keith A.
Abstract: Understanding non‐breeding season movements and identifying wintering areas of different populations of migratory birds is important for establishing patterns of migratory connectivity over the annual cycle. We analyzed archival solar geolocation ( N  = 5) and global positioning data ( N  = 1) to investigate migration routes, stopover sites, and wintering areas of a western‐most breeding population of Veeries ( Catharus fuscescens ) in the Pemberton Valley, British Columbia, Canada. Geolocation data were analyzed using a Bayesian state‐space model to improve likely position estimates. We compared our results with those from a Veery population located ~250 km east across a mountain chain in the Okanagan Valley, British Columbia, and with an eastern population in Delaware, U.S.A. Migrating Veeries from the Pemberton Valley used an eastern trajectory through the Rocky Mountains to the Great Plains to join a central flyway during fall and spring migration, a route similar to that used by Veeries breeding in the Okanagan Valley. However, wintering destinations of Pemberton Valley birds were more varied, with inter‐individual wintering distances ~1000 km greater than birds from the Okanagan Valley population and ~500 km from the previously known winter range of Veeries. The observed eastern migration path likely follows an ancestral route that evolved following the most recent glacial retreat. Consistent with patterns observed from the Okanagan and Delaware populations, Veeries from the Pemberton Valley undertook an intra‐tropical migration on the wintering grounds, but this winter movement differed from those of previously studied populations. Such winter movements may thus be idiosyncratic or show coarse population associations. Intra‐wintering‐ground movements likely occur either in response to seasonal changes in habitat suitability or as a means of optimizing pre‐migratory fueling prior to long‐distance spring movements to North America.